An indium-based thermally conductive interface material-integrated heat dissipation cover assembly and a preparation method thereof
Patent Information
- Application Number
- CN202610777068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-01
- Publication Date
- 2026-09-25
AI Technical Summary
[0003]然而,现有预组装方案存在显著的技术缺陷
[0152]1. 成本降低:相比真空非破空工艺,本发明仅需常规涂布设备,设备成本降低约60-90%。相比金保护层工艺,本发明无贵金属消耗,材料成本降低约90%以上。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor packaging technology, and more specifically, to an indium-based thermal interface material-integrated heat sink assembly and its fabrication method. This invention is particularly applicable to thermal management applications in high-performance computing chips, graphics processors, artificial intelligence accelerators, power modules, and other high-power semiconductor devices. Background Technology
[0002] Pure indium possesses excellent thermal conductivity (approximately 81.8 W / m·K) and a moderate melting point (156.6°C). Indium-based thermal interface materials therefore combine high thermal conductivity, good ductility, and low processing temperature, making them widely used in high-performance chip packaging. Pre-assembling indium-based thermal interface materials onto integrated heat sinks as sub-components for downstream users simplifies the packaging process, reduces pick-and-place steps, and improves production efficiency and consistency.
[0003] However, existing pre-assembly solutions have significant technical drawbacks. On the one hand, some solutions require indium to be integrated onto the nickel layer immediately after it has been formed on the surface of the integrated heat sink, without disrupting the vacuum, or integration to be completed in an air-isolated environment such as an inert atmosphere glove box. Such vacuum / inert environment processes significantly increase equipment costs, reduce manufacturing flexibility, and limit the economic feasibility of large-scale mass production. On the other hand, other solutions use a protective layer of precious metals such as gold on the nickel layer to prevent oxidation, but the use of gold further increases material costs and introduces additional process steps.
[0004] Therefore, there remains an urgent need for an indium-based thermal interface material—an integrated heat sink assembly—supplied by a supplier, which can attach indium to the integrated heat sink via a simple organic adhesive layer containing an activator after the nickel layer has been formed and exposed to ambient air, without the need for vacuum non-destructive or air isolation processes, or the need for a precious metal protective layer, while still achieving reliable metallurgical bonding and excellent thermal conductivity in subsequent reflow processes performed by the end user. Summary of the Invention
[0005] This invention provides an indium-based thermally conductive interface material-integrated heat dissipation cover assembly and its preparation method.
[0006] The core concept of this invention lies in the following: by placing an organic binder containing an activator between the nickel layer of an integrated heat sink already exposed to ambient air (i.e., a nickel oxide layer has naturally formed on the surface) and the indium-based thermally conductive interface material, indium can reliably adhere to the nickel layer without the need for a vacuum environment or a precious metal protective layer. During the supplier stage, this organic binder only provides temporary adhesion and oxide layer modification functions, without forming a metallurgical bond. In the end-user's subsequent reflow process, the organic binder at least partially decomposes, volatilizes, or diffuses into the indium-based thermally conductive layer, while a strong metallurgical bond forms between the indium and the nickel layer. This two-stage design (only physical / chemical adhesion during the supplier pre-assembly stage, and metallurgical bonding during the user reflow stage) is one of the core features that distinguishes this invention from existing technologies.
[0007] In addition, the activator in the organic adhesive layer can weaken, modify or partially remove the nickel oxide that naturally forms on the surface of the nickel layer, solving the technical problem of the oxide layer hindering adhesion after exposure to air.
[0008] This invention provides an indium-based thermally conductive interface material-integrated heat dissipation cover assembly, comprising:
[0009] Integrated heat sink
[0010] The integrated heat sink is made of copper, copper alloy, or other high thermal conductivity metals with a thermal conductivity >200 W / m·K. Optional materials include copper-molybdenum composites, copper-tungsten composites, and aluminum-silicon carbide composites. The integrated heat sink can be flat or have a recessed structure, with the recess depth typically ranging from 50-800 μm to accommodate indium-based thermal interface materials.
[0011] Nickel layer
[0012] A nickel layer is formed on at least one surface of the integrated heat sink, typically the inner surface facing the chip. The functions of the nickel layer include: (i) acting as a diffusion barrier layer to prevent copper in the integrated heat sink from diffusing into the indium layer to form a high-resistivity, highly brittle Cu-In intermetallic compound; (ii) acting as a wettable surface to form a Ni-In intermetallic compound metallurgical bond with indium; and (iii) acting as an anti-oxidation protective layer, as nickel oxidizes at a slower rate than copper.
[0013] The nickel layer can be formed by electroplating, electroless plating, or physical vapor deposition. The thickness of the nickel layer is from 2 μm to 20 μm, preferably from 4 μm to 10 μm. If it is too thin, the diffusion barrier effect will be insufficient; if it is too thick, the cost will increase and it may lead to peeling due to internal stress. The surface roughness Ra of the nickel layer is 0.05-1.0 μm. Appropriate roughness helps to increase the mechanical interlocking with the organic binder layer.
[0014] Organic adhesive layer
[0015] An organic binder layer is disposed on the surface of the nickel layer and contains one or more activators. The thickness of the organic binder layer is from 10 nm to 3 μm, preferably from 100 nm to 1000 nm.
[0016] Indium-based thermally conductive interface material layer
[0017] An indium-based thermally conductive interface material layer is attached to the nickel layer via an organic adhesive layer. The material is pure indium (purity >99.99%) or an indium-based alloy. The thickness of the indium-based thermally conductive interface material is 50 μm to 800 μm, preferably 150 μm to 500 μm.
[0018] Key structural features:
[0019] - (i) The indium-based thermal interface material is attached to the integrated heat sink (pre-assembled by the supplier) before being delivered to the end user.
[0020] - (ii) The organic adhesive layer enables indium to adhere after the nickel layer has been exposed to ambient air (no vacuum required, no gold layer required).
[0021] - (iii) The indium-based thermal interface material is configured to form a metallurgical bond with the integrated heat sink in the end-user's reflow process.
[0022] The organic adhesive layer performs four core functions in this invention:
[0023] 1. Temporary adhesion function: Provides sufficient adhesion to keep the indium sheet in a predetermined position on the integrated heat sink.
[0024] 2. Oxide layer modification function: The activator interacts chemically with NiO on the surface of the nickel layer, weakening or modifying the oxide layer.
[0025] 3. Antioxidant protection function: Forms a thin physical barrier to slow down the secondary oxidation of the nickel layer.
[0026] 4. Removable function: It can decompose, volatilize, or diffuse into the indium-based thermal conductive layer at reflow temperature.
[0027] Specific types of activators
[0028] An activator is an organic compound that can chemically interact with metal oxides. Unlike conventional fluxes, the activator in this invention is designed to be non-corrosive, requiring only the weakening or modification of the oxide layer to prevent it from hindering wetting, rather than completely removing the oxide.
[0029] Type I: Organic carboxylic acids
[0030] The general formula for organic carboxylic acids is R-COOH. The carboxylic acid group (-COOH) can react with metal oxides. Representative compounds include: formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, malic acid, tartaric acid, citric acid, lactic acid, glycolic acid, acrylic acid, methacrylic acid, and combinations thereof.
[0031] Type II: Organic Amines
[0032] Organic amines have the general formula R-NH2, R2-NH, or R3N and can coordinate with metal oxides. Representative compounds include: n-butylamine, hexylamine, octylamine, diethylamine, triethylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, monoethanolamine, diethanolamine, triethanolamine, and combinations thereof.
[0033] Type III: Organophosphates / phosphonic acids
[0034] Organophosphoric acid compounds have a strong chelating ability for metal oxides. Representative compounds include aminotrimethylphosphonic acid (ATMP), hydroxyethylidene diphosphonic acid (HEDP), ethylenediaminetetramethylphosphonic acid (EDTMP), and combinations thereof.
[0035] Type IV: Organic sulfonic acids
[0036] Organic sulfonic acids have the general formula R-SO3H, and representative compounds include p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and combinations thereof.
[0037] Type V: Aminocarboxylic acid
[0038] Aminocarboxylic acids are chelating ligands that combine amino and carboxyl groups. Representative compounds include ethylenediaminetetraacetic acid (EDTA), nitrotriacetic acid (NTA), and combinations thereof.
[0039] Type VI: Thiols
[0040] The thiol compounds include alkyl thiols (such as dodecanethiol, octetrate, and octadecethiol), aryl thiols (such as thiophenol and benzyl thiols), and polythiols (such as 1,2-ethanedithiol and 1,6-hexanedithiol) and combinations thereof.
[0041] 2. Solvent
[0042] Solvents are used to dissolve or disperse activators and to adjust the application viscosity and drying properties of the binder layer. Representative solvents include: methanol, ethanol, isopropanol, butanol, acetone, butanone, ethyl acetate, butyl acetate, ethylene glycol ether, propylene glycol ether, toluene, xylene, deionized water, and mixtures thereof.
[0043] 3. Film-forming agent
[0044] Film-forming agents are used to improve the mechanical integrity and adhesion of organic adhesive layers. Representative film-forming agents include: rosin, modified rosin, shellac, polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylic acid, polyacrylamide, methylcellulose, hydroxyethylcellulose, sodium carboxymethylcellulose, paraffin wax, microcrystalline wax, polyethylene wax, and combinations thereof.
[0045] 4. Additives
[0046] Organic adhesive layers may also contain a variety of functional additives: antioxidants (such as BHT and vitamin E), leveling agents (such as silicone surfactants), defoamers (such as polydimethylsiloxane), plasticizers (such as phthalates and adipates), and combinations thereof.
[0047] 5. Preferred composition range of the organic adhesive layer
[0048] According to the present invention, the composition of the organic adhesive layer can be varied within the following ranges:
[0049] - Activator: 0.01-20 wt% (preferably 0.1-10 wt%, more preferably 0.5-5 wt%)
[0050] - Solvent: 50-99.9 wt% (preferably 70-98 wt%, more preferably 85-95 wt%)
[0051] - Film-forming agent: 0-30 wt% (preferably 0.1-15 wt%, more preferably 0.5-5 wt%)
[0052] - Other additives: 0-5 wt% (preferably 0-2 wt%)
[0053] Mechanism of action of activators
[0054] This invention is not limited to any particular theory, but the following mechanisms of action are believed to help in understanding the technical effects of this invention.
[0055] Mechanism 1: Oxide weakening / modification mechanism
[0056] Reactive functional groups in activator molecules (such as carboxyl-COOH, hydroxyl-OH, phosphonic acid-PO3H2, sulfonic acid-SO3H, and amino-NH2) can interact with NiO oxide on the nickel layer surface. These interactions may include: the reaction of carboxylic acids with nickel oxide to form nickel carboxylate salts and water; the coordination of amines with nickel oxide to form surface coordination complexes; and the reaction of phosphonic acids with nickel oxide to form nickel phosphonate and water. All of these reactions produce water, which can evaporate and escape from the system. More importantly, these reactions only consume a portion of the oxide layer, without requiring complete removal of the oxide. This is fundamentally different from the traditional flux principle of "complete oxide removal."
[0057] Mechanism 2: Wetting Promotion Mechanism
[0058] Certain components in the organic binder layer can act as surfactants, reducing the interfacial tension between the molten indium and the nickel surface, thereby promoting wetting and spreading. Even in the presence of a residual oxide layer, indium can spread on it and locally contact the underlying metallic nickel, triggering metallurgical bonding.
[0059] Mechanism 3: Oxygen Shielding Mechanism
[0060] The organic binder layer forms a physical barrier, preventing oxygen in the air from contacting the nickel layer surface during subsequent processing, thereby slowing down the secondary oxidation rate.
[0061] Application method of organic adhesive layer
[0062] Organic adhesive layers can be applied in various ways:
[0063] Spraying method: The organic binder is atomized and sprayed onto the surface of the nickel layer, which is suitable for large-area uniform coating.
[0064] Dip coating method: The integrated heat sink is immersed in an organic adhesive liquid and then lifted out. The film thickness is adjusted by controlling the lifting speed and the viscosity of the adhesive liquid.
[0065] Spin coating: An organic binder is dropped onto the center of a nickel layer and then rotated at high speed to form a uniform thin layer.
[0066] Printing method: The organic adhesive liquid is transferred onto the nickel layer surface by screen printing or pad printing.
[0067] Dot coating method: Apply only to specific areas (such as covering only the pit area or only the area where indium is to be placed).
[0068] The drying conditions (temperature, time, atmosphere) after application should be adjusted according to the type of solvent, usually drying for several seconds to several minutes at room temperature to 100°C in air or nitrogen atmosphere to remove the solvent and form a dry organic binder layer.
[0069] Thickness range and optimization of organic adhesive layer
[0070] The thickness of the organic adhesive layer is a key process parameter.
[0071] - Less than 10 nm: may not be sufficient to cover the microstructure of the nickel layer surface, and the oxide modification effect is insufficient.
[0072] - 10-100 nm: can achieve basic adhesion promotion effect, but may not provide sufficient antioxidant protection.
[0073] - 100-1000 nm (preferred range): balances oxide modification effect, adhesion and antioxidant protection, while minimizing residue during reflow.
[0074] - 1-3 μm: Strong adhesion and excellent antioxidant protection, but the risk of residue is slightly increased.
[0075] - Greater than 3 μm: Organic residues may remain due to incomplete decomposition of film-forming agents or activators, affecting metallurgical bonding.
[0076] Therefore, the optimal thickness range is 100-1000 nm.
[0077] Nickel layer
[0078] The nickel layer is a key functional layer in the pre-assembled components of this invention, ensuring reliable adhesion and long-term stability. The nickel layer can be formed by methods such as electroplating, electroless plating (electro-free nickel plating), or physical vapor deposition (PVD, such as sputtering or evaporation). The key parameters of the nickel layer and their technical implications are described in detail below.
[0079] (a) Nickel layer thickness
[0080] The thickness of the nickel layer is one of the core parameters affecting the performance and reliability of the component. In this invention, the thickness of the nickel layer is 2 μm to 20 μm, preferably 4 μm to 10 μm.
[0081] - Technical considerations regarding the minimum thickness: When the nickel layer thickness is less than 2 μm, it is difficult to form a continuous and dense capping layer. Microscopic defects such as pinholes and cracks may exist in the nickel layer. These defects can become rapid channels for copper diffusion into the indium layer, leading to the formation of high-resistivity and highly brittle Cu-In intermetallic compounds (mainly CuIn and Cu2In) during reflow or subsequent high-temperature service conditions. The thermal conductivity of these intermetallic compounds is much lower than that of pure indium and pure copper (CuIn's thermal conductivity is approximately 20-30 W / m·K), significantly increasing interfacial thermal resistance and reducing reliability. Furthermore, an excessively thin nickel layer may crack due to stress fatigue during long-term thermal cycling, losing its diffusion-blocking function.
[0082] - Technical considerations regarding the upper limit of thickness: When the nickel layer thickness exceeds 20 μm, although the diffusion barrier capability is further enhanced, it will bring two problems: First, the internal stress of the nickel layer accumulates with the increase of thickness. The internal stress of electroplated nickel can reach 100-200 MPa. An excessively thick nickel layer may lead to a decrease in the bonding force between the nickel layer and the copper substrate of the integrated heat sink, or even spontaneous peeling. Second, although the thermal conductivity of nickel itself (about 90-100 W / m·K) is relatively high, it is still lower than that of copper (about 400 W / m·K). An excessively thick nickel layer will introduce additional thermal resistance (according to Fourier's law, thermal resistance is proportional to thickness), thereby reducing the overall heat dissipation efficiency.
[0083] - The preferred range of 4-10 μm is based on the fact that this preferred range balances diffusion barrier effect, internal stress control, and thermal resistance minimization. Within this thickness range, low internal stress (<50 MPa) and high density nickel layers can be obtained by optimizing the electroplating process (e.g., using an aminosulfonate nickel plating bath instead of a watt bath).
[0084] (ii) Surface roughness of nickel layer
[0085] The surface roughness of the nickel layer directly affects the uniformity of the organic adhesive layer and the adhesion effect of the indium-based thermally conductive interface material. In this invention, the surface roughness Ra of the nickel layer is preferably 0.05-1.0 μm.
[0086] - Effects of excessively low surface roughness (<0.05 μm): When the surface is too smooth, the mechanical interlocking (anchoring effect) between the organic adhesive layer and the nickel layer is weakened, and the adhesion mainly depends on chemical bonding and van der Waals forces. During subsequent handling and vibration, the indium sheet may slip due to insufficient interfacial shear strength. At the same time, an overly smooth surface is also not conducive to the spread of the activator, which may lead to poor local wetting.
[0087] - Effects of excessively rough surfaces (>1.0 μm): When the surface is too rough, the organic binder layer may accumulate too thickly in the valleys, while uncovered nickel layer areas may be exposed at the peaks. This uneven coverage leads to two problems: first, the peaks are directly exposed to air, which may cause localized oxidation, affecting indium adhesion; second, the organic binder layer accumulated in the valleys may produce localized residues during reflow due to incomplete decomposition, hindering the formation of metallurgical bonds. Furthermore, the excessively rough nickel layer surface has sharp micro-protrusions that may puncture the indium sheet during lamination, affecting interface integrity.
[0088] - Determination of the preferred range: Ra 0.05-1.0 μm (preferably 0.1-0.5 μm) is an industrially feasible range with optimal overall performance. This roughness range can be precisely controlled by adjusting the electroplating current density (2-5 A / dm²), plating bath temperature (40-60°C), and the amount of additives used.
[0089] (III) Explanation of the substitutability of the nickel layer
[0090] Although this invention is described using a nickel layer as a diffusion barrier, those skilled in the art will understand that other metal layers with similar functions (such as cobalt (Co), molybdenum (Mo), titanium (Ti), tungsten (W), or alloys thereof) can also replace the nickel layer, provided that these metal layers can: (i) effectively block copper diffusion into the indium layer; (ii) form a suitable metallurgical bond with indium; and (iii) have an acceptable oxidation rate. These alternatives all fall within the scope of this invention.
[0091] Indium-based thermally conductive interface material layer
[0092] The indium-based thermally conductive interface material layer (indium-based TIM layer) is the core functional layer for achieving high thermal conductivity in this invention. Its material, alloying elements, thickness, shape, and surface condition are described in detail below.
[0093] (a) Material selection
[0094] In this invention, the indium-based thermally conductive interface material layer is made of pure indium or an indium-based alloy.
[0095] Pure indium: The purity is preferably greater than 99.99%. High-purity indium has the lowest impurity content, which can maximize the preservation of indium's intrinsic thermal conductivity (approximately 81.8 W / m·K) and excellent ductility (elongation >50%). The presence of impurities (such as Pb, Cd, Tl, etc.) not only reduces the thermal conductivity, but may also change the melting point or form low-melting-point eutectics at the interface, reducing thermal stability.
[0096] Indium-based alloys: In certain specific applications, the mechanical properties (such as creep resistance) or melting point characteristics of pure indium may not fully meet the requirements. In such cases, the properties of indium can be adjusted by adding small amounts of alloying elements. Alloying is a trade-off design—while improving certain properties, thermal conductivity is often slightly sacrificed; therefore, the total amount of alloying elements added should be controlled within a reasonable range.
[0097] (II) Types and Functions of Alloying Elements
[0098] In this invention, the alloying elements that can be added to indium are selected from Bi, Ag, Co, Cu, Zn, Ga, Sn, and combinations thereof, and the total amount of alloying elements added does not exceed 5 wt%, preferably not exceeding 2 wt%. The functions of each alloying element and the considerations for its addition are as follows:
[0099] Bi (bismuth):
[0100] - Function: Significantly reduces the melting point of indium. The In-Bi binary phase diagram shows that when the Bi content is 2 wt%, the melting point can be reduced to approximately 140°C; when the Bi content is 5 wt%, the melting point can be further reduced to approximately 130°C. The lower melting point facilitates the molten spreading of indium in reflow processes at lower temperatures, reducing thermal stress on other heat-sensitive components in the package.
[0101] - Side effects: The addition of Bi will reduce the thermal conductivity of indium (by about 5-10%), and excessive Bi content (>5wt%) will form brittle In-Bi intermetallic compounds, reducing the ductility of the material.
[0102] - Preferred content: 0.5-3 wt%, more preferably 0.5-2 wt%.
[0103] Ag (silver):
[0104] - Function: To improve the strength and creep resistance of indium. In In-Ag alloys, Ag exists in solid solution within the indium matrix, enhancing the material's high-temperature creep resistance through a solid solution strengthening mechanism. During thermal cycling, pure indium is prone to creep deformation and extrusion, while the addition of Ag significantly mitigates this problem.
[0105] - Side effects: The addition of Ag increases the melting point of the alloy (In-1Ag melting point is about 160°C, In-3Ag melting point is about 170°C) and increases material costs.
[0106] - Preferred content: 1-4 wt%, more preferably 1-3 wt%.
[0107] Co (Cobalt):
[0108] - Function: To inhibit the excessive growth of Ni-In intermetallic compounds. Co can act as a diffusion barrier layer by forming Co-In compounds or segregating at the interface, slowing down the interdiffusion rate between Ni and In, thereby controlling the thickness growth of the Ni-In intermetallic compound layer. This is especially important under long-term high-temperature service conditions.
[0109] - Side effects: Co is insoluble in indium and exists in indium as fine particles, which may slightly increase interfacial thermal resistance.
[0110] - Preferred content: 0.1-2 wt%, more preferably 0.2-1 wt%.
[0111] Cu (copper):
[0112] - Function: Similar to Co, Cu can also suppress the excessive growth of intermetallic compounds by forming Cu-In compounds or by forming a diffusion barrier layer at the interface. In addition, the addition of Cu can improve the mechanical strength of indium.
[0113] - Side effects: Cu has extremely low solubility in indium (<0.1 wt%). Excess Cu will precipitate in the form of brittle phases such as CuIn2, reducing the toughness of the material.
[0114] - Preferred content: 0.1-2 wt%, more preferably 0.2-1 wt%.
[0115] Zn (zinc):
[0116] - Function: Zn lowers the melting point of indium (In-2Zn melting point is approximately 140°C) while improving the wettability of indium on nickel surfaces. The addition of Zn also helps reduce the surface tension of indium, promoting its spreading.
[0117] - Side effects: Zn has high chemical reactivity and is easily oxidized, which may increase the thickness of the oxide layer on the surface of the thermal interface material and place higher demands on the treatment of the organic binder layer.
[0118] - Preferred content: 0.5-3 wt%.
[0119] Ga (gallium):
[0120] - Function: Ga forms a completely miscible solid solution with In, which can lower the melting point of the alloy (In-5Ga melting point is about 130°C) while maintaining high ductility. The addition of Ga can also improve the oxidation resistance of indium (because Ga preferentially oxidizes to form a dense Ga2O3 protective film).
[0121] - Side effects: Ga is expensive and Ga2O3 has a high melting point (about 1900°C). Once formed, it is difficult to remove and requires the use of stronger activators (such as organophosphonic acids) in the organic binder layer for treatment.
[0122] - Preferred content: 1-5 wt%.
[0123] Sn (tin):
[0124] - Function: Sn and In form an In-Sn eutectic system, which can adjust the melting point (In-1Sn melting point is about 155°C, In-5Sn melting point is about 140°C) and improve mechanical properties.
[0125] - Side effects: Excessive Sn can lead to the formation of brittle In-Sn intermetallic compounds (such as InSn4), reducing ductility.
[0126] - Preferred content: 1-4 wt%.
[0127] Examples of synergistic effects in multi-element alloys:
[0128] - In-1Ag-0.5Bi: It combines the strength improvement of Ag with the lower melting point of Bi, resulting in excellent overall performance.
[0129] - In-3Ag-0.5Cu: For high-temperature service scenarios, it enhances creep resistance and intermetallic compound suppression.
[0130] - In-1Co-0.5Bi: Focuses on long-term reliability, using Co to control the growth of intermetallic compounds.
[0131] (III) Table 1 Typical alloy systems and their application scenarios
[0132] Pure In In 100 156.6 81.8 Universal type, lowest cost In-1Ag In 99, Ag 1 160 80-85 Improve thermal cycling performance In-3Ag In 97, Ag 3 170 75-80 High strength requirements In-0.5Bi In 99.5%, Bi 0.5 152 82-86 Low temperature reflux, good ductility In-2Bi In 98, Bi 2 140 78-82 Low-temperature reflux improves wettability In-1Cu In 99, Cu 1 155 80-85 Intermetallic compound inhibition In-1Co In 99, Co 1 155 80-85 Long-term high-temperature service In-1Ag-0.5Bi In 98.5%, Ag 1%, Bi 0.5% 155 80-85 Excellent overall performance
[0133] (iv) Thickness of the indium-based thermally conductive interface material layer
[0134] The thickness of the indium-based thermal interface material layer is a key parameter affecting thermal resistance, compliance, and process cost. In this invention, the thickness of the indium-based thermal interface material layer is 50 μm to 800 μm, preferably 150 μm to 500 μm.
[0135] - Technical considerations regarding the minimum thickness: When the thickness is less than 50 μm, the thermal capacity and deformation capability of the indium layer are insufficient. During the lamination process, the thin indium layer cannot fully fill the microscopic unevenness (including surface roughness, warpage, particles, etc.) between the chip and the integrated heat sink, resulting in air gaps at the interface and increasing contact thermal resistance. In addition, the thin indium layer is more prone to losing continuity due to creep depletion during long-term thermal cycling.
[0136] - Technical considerations regarding thickness limits: While compliance is excellent when the thickness exceeds 800 μm, the amount of indium used is large, significantly increasing costs. Furthermore, excessively thick indium layers may experience lateral extrusion during reflow, contaminating the packaging substrate or adjacent components. Additionally, indium's thermal conductivity (81.8 W / m·K) is much lower than copper's (400 W / m·K), meaning excessively thick indium layers introduce additional bulk thermal resistance.
[0137] - The preferred thickness range of 150-500 μm is chosen because this range strikes the best balance between cost control, minimizing thermal resistance, and maximizing compliance. For most CPU / GPU packages, 300 μm is the most commonly used value in industrial practice. For large chips (>20×20 mm) or power modules with significant warpage, a thickness of 400-500 μm can be used to ensure sufficient fill; for smaller chips (<10×10 mm) or packages with well-controlled warpage, a thinner layer of 150-250 μm is sufficient.
[0138] Preparation method
[0139] A method for preparing an integrated heat dissipation cover assembly using an indium-based thermally conductive interface material provided by a supplier includes the following steps:
[0140] Step 1: Nickel layer formation steps
[0141] A nickel layer is formed on the integrated heat sink. Electroplating (Watt bath, sulfamate bath), electroless plating (electro-free nickel plating), or PVD (sputtering, evaporation) methods can be used. Electroplating temperature: 40-60°C, current density: 1-5 A / dm²; Electroless plating temperature: 50-90°C, pH: 3-5 or 8-10.
[0142] Step 2: Exposure Step
[0143] The nickel layer is exposed to ambient air, allowing the nickel oxide layer to form naturally. Conditions include normal air pressure, relative humidity of 20-80%, temperature of 15-35°C, and time ranging from 1 minute to 30 days.
[0144] Step 3: Application of the organic adhesive layer
[0145] Before indium is applied, an organic binder containing an activator is applied to the nickel layer to weaken, modify, or partially remove the naturally formed nickel oxide layer. Application methods include spraying, dip coating, spin coating, printing, or dot coating. Drying parameters: temperature from room temperature to 100°C (preferably 40-80°C), time from 10 seconds to 10 minutes (preferably 30 seconds to 3 minutes).
[0146] Step 4: Indium adhesion step
[0147] An indium-based thermally conductive interface material is attached to a nickel layer using an organic adhesive layer. The method can be selected from lamination, pressing, or simple placement. The pressure is 0.01-1 MPa (preferably 0.05-0.2 MPa), the temperature is room temperature to 100°C (should be below the activation temperature to avoid premature metallurgical bonding), and the time is 0.1-10 seconds.
[0148] Step 5: Post-processing steps
[0149] This includes inspection, drying, and packaging. Inspection can be performed using automated optical inspection to verify the position and alignment of the indium wafers; drying conditions are 50-80°C for 10-30 minutes; packaging is done in an inert atmosphere or in dry air and sealed.
[0150] The metallurgical bond between the indium-based thermal interface material and the integrated heat sink is formed during the reflow process subsequently performed by the end user.
[0151] Compared with the prior art, the present invention has the following beneficial effects:
[0152] 1. Cost Reduction: Compared to vacuum non-cavitation processes, this invention only requires conventional coating equipment, reducing equipment costs by approximately 60-90%. Compared to gold protective layer processes, this invention consumes no precious metals, reducing material costs by over 90%.
[0153] 2. Increased process flexibility: After the nickel layer is exposed to air, subsequent processing can be completed within 30 days, without the need for strict time window restrictions.
[0154] 3. Thermal performance retention: After reflow, the thermal resistance of the indium-based thermally conductive interface material is comparable to that of conventional processes (interface thermal resistance <0.1 K·cm² / W), and the organic binder residue is less than 0.1 wt%.
[0155] 4. Mechanical reliability: Shear strength after reflow ≥10 MPa, meeting the requirements of industrial applications.
[0156] 5. Storage stability: After being stored at room temperature for 6 months under a nitrogen atmosphere and sealed packaging, it still maintains good adhesion with an adhesion decrease of no more than 20%. Detailed Implementation
[0157] The present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto.
[0158] Example 1
[0159] Step 1: Nickel layer formation
[0160] A copper integrated heat sink (20×20 mm) was selected, and a nickel layer was formed on its surface by electroplating. Electroplating conditions: watt bath, current density 3 A / dm², temperature 50°C, electroplating time 15 minutes, resulting in a nickel layer thickness of approximately 5 μm. The nickel-plated integrated heat sink was then cleaned with deionized water and dried with nitrogen.
[0161] Step 2: Ambient Air Exposure
[0162] The nickel-plated integrated heat sink was exposed to ambient air for 72 hours (temperature 25°C, relative humidity 50%), allowing a nickel oxide layer to form naturally on the surface of the nickel layer.
[0163] Step 3: Preparation and application of organic adhesive layer
[0164] Prepare the organic binder solution: 2 wt% adipic acid (activator) + 2 wt% polyvinyl alcohol (film-forming agent) + 96 wt% ethanol (solvent), stir until completely dissolved.
[0165] The aforementioned organic binder was applied to the nickel layer surface of the integrated heat sink using a spraying method. The spraying parameters were: nozzle diameter 0.3 mm, spraying pressure 0.2 MPa, and spraying distance 10 cm. After drying at 80°C for 30 seconds, the organic binder layer thickness was approximately 150 nm.
[0166] Step 4: Indium attachment
[0167] A pure indium sheet with a thickness of approximately 300 μm (purity 99.99%) is selected and placed on the nickel layer of the integrated heat sink that has been treated as described above. A pressure of 0.1 MPa is applied for 2 seconds to press the indium sheet onto the integrated heat sink, thus obtaining a pre-assembled component.
[0168] Step 5: Post-processing
[0169] The pre-assembled components were dried at 60°C for 15 minutes and then sealed in a nitrogen atmosphere.
[0170] Example 2
[0171] Based on Example 1, prior to step 4, the indium sheet is also dipped in the same organic binder to form an organic binder layer of approximately 200 nm on both sides of the indium sheet. The indium sheet is then pressed onto the nickel layer of the integrated heat sink. The remaining steps are the same as in Example 1.
[0172] Example 3
[0173] The pure indium sheet in Example 1 was replaced with an In-1Ag alloy sheet (250 μm thick, 1 wt% Ag content), and the remaining steps were the same as in Example 1.
[0174] Example 4
[0175] Prepare the organic binder solution: 2 wt% glutaric acid (activator) + 2 wt% polyvinyl alcohol (film-forming agent) + 96 wt% ethanol (solvent), stir until completely dissolved. The remaining steps are the same as in Example 1.
[0176] Example 5
[0177] Prepare the organic binder solution: 2 wt% dodecyl mercaptan (activator) + 98 wt% ethanol (solvent), stir until completely dissolved. The remaining steps are the same as in Example 1.
[0178] Example 6
[0179] The electroplating time in Example 1 was adjusted to 30 minutes, resulting in a nickel layer thickness of approximately 10 μm. The remaining steps were the same as in Example 1.
[0180] Example 7
[0181] Replace the thickness of the pure indium sheet in Example 1 with 500 μm. The remaining steps are the same as in Example 1.
[0182] Comparative Example 1
[0183] After the integrated heat sink was nickel-plated and exposed to air for 72 hours, an indium sheet was placed directly without an organic adhesive layer and pressed together with a pressure of 0.1 MPa for 2 seconds. Result: The indium sheet failed to adhere and detached with the slightest touch.
[0184] Comparative Example 2
[0185] The integrated heat sink is nickel-plated and does not expose air. Indium sheets are directly pressed into the heat sink in a vacuum (<1×10⁻³ Pa) without an organic adhesive layer. Result: Good adhesion. However, the equipment cost is significantly higher than that of this invention.
[0186] Comparative Example 3
[0187] After nickel plating on the integrated heat sink, a 0.1 μm layer of gold was electroplated onto the nickel layer, and the surface was exposed to air for 72 hours. No organic adhesive layer was used, and an indium sheet was then laminated onto it. Result: Good adhesion. However, the gold layer was more expensive.
[0188] Performance testing
[0189] The pre-assembled components prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to reflow treatment in air: the temperature was raised to 200°C, held for 2 minutes, and a pressure of 0.2 MPa was applied. The bonding state, shear strength, and thermal resistance before and after reflow were tested.
[0190] Test method:
[0191] - Initial adhesion evaluation: Visually inspect whether the indium sheet remains in place and whether it detaches upon light touch.
[0192] - Shear strength test: The shear strength tester was used in accordance with the JIS Z 3198 standard.
[0193] - Thermal resistance test: Measured using a thermal resistance tester in accordance with ASTM D5470 standard.
[0194] Test results:
[0195] Table 2 Comparison of performance test results between each embodiment and the comparative example
[0196]
[0197] Test results show that the embodiments of the present invention achieve comparable levels to Comparative Example 2 (vacuum process) and Comparative Example 3 (gold protective layer) in terms of initial adhesion, shear strength after reflow, and thermal resistance, but with significantly reduced costs.
[0198] Storage stability test
[0199] The pre-assembled components prepared in Example 1 were sealed in a nitrogen atmosphere and stored at room temperature for 6 months. After 6 months, they were removed, refluxed, and their shear strength and thermal resistance were tested.
[0200] Test results: After 6 months of storage, the shear strength was 11.8 MPa (initially 12.5 MPa, with a decrease of approximately 5.6%), and the thermal resistance was 0.09 K·cm² / W (initially 0.08 K·cm² / W), still meeting the requirements for industrial applications. This indicates that the pre-assembled component of this invention has good storage stability.
[0201] Analysis of organic adhesive layer residues
[0202] Thermogravimetric analysis (TGA) was performed on the sample after reflow in Example 1. The mass loss was less than 0.1 wt% when heated below 300°C, indicating that the content of organic binder residue was extremely low and would not have a substantial impact on thermal conductivity.
[0203] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered to be within the protection scope of the present invention.
Claims
1. An indium-based thermally conductive interface material-integrated heat dissipation cover assembly, comprising: An integrated heat sink has a nickel layer formed on its surface; And an indium-based thermally conductive interface material, which is attached to the nickel layer via an organic adhesive layer, characterized in that: The indium-based thermal interface material has been attached to the integrated heat sink before being delivered to the end user. The organic adhesive layer allows for the adhesion of the indium-based thermally conductive interface material after the nickel layer has been exposed to ambient air; and The indium-based thermal interface material is configured to form a metallurgical bond with the integrated heat sink during a reflow process subsequently performed by the end user.
2. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The organic adhesive layer contains one or more activators selected from organic carboxylic acids, organic sulfonic acids, organic phosphoric acids, organic phosphonic acids, organic amines, thiols, and combinations thereof.
3. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 2, characterized in that: The organic carboxylic acids are selected from: formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, malic acid, tartaric acid, citric acid, lactic acid, glycolic acid, acrylic acid, methacrylic acid, and combinations thereof; the organic amines are selected from: n-butylamine, hexylamine, octylamine, diethylamine, triethylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, monoethanolamine, diethanolamine, triethanolamine, and combinations thereof; the organic phosphoric acid is selected from: aminotrimethylphosphonic acid (ATMP), hydroxyethylidene diphosphonic acid (HEDP), ethylenediaminetetramethylphosphonic acid (EDTMP), and combinations thereof; the thiols are selected from: dodecanethiol, octetratethiol, octadecylthiol, benzylthiophenol, benzylthiol, 1,2-ethylenedithiol, 1,6-hexanedithiol, and combinations thereof.
4. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The organic adhesive layer further comprises a film-forming agent selected from rosin, modified rosin, polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, cellulose, and combinations thereof.
5. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The thickness of the organic adhesive layer is 10 nm to 3 μm.
6. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The thickness of the nickel layer is 2 μm to 20 μm.
7. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The thickness of the indium-based thermally conductive interface material is from 50 μm to 800 μm.
8. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: The indium-based thermal interface material contains one or more alloying elements, which are selected from Bi, Ag, Co, Cu, Zn, Ga, Sn and combinations thereof, with a total amount not exceeding 5 wt%.
9. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: Before attaching the indium-based thermally conductive interface material, the application of the organic adhesive layer weakens, modifies, or partially removes the nickel oxide layer that naturally forms on the surface of the nickel layer due to exposure to ambient air, thereby facilitating the wetting and bonding of the indium-based thermally conductive interface material.
10. The indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to claim 1, characterized in that: An organic adhesive layer is also provided on the surface of the indium-based thermally conductive interface material facing the nickel layer and / or the surface away from the nickel layer.
11. A method for preparing an indium-based thermally conductive interface material-integrated heat dissipation cover assembly according to any one of claims 1 to 10, characterized in that, Includes the following steps: A nickel layer is formed on the integrated heat sink; The nickel layer is exposed to ambient air, thereby allowing a nickel oxide layer to form naturally on the surface of the nickel layer. Before attaching the indium-based thermal interface material to the integrated heat sink, an organic binder layer containing one or more activators is applied to the nickel layer to weaken, modify, or partially remove the naturally formed nickel oxide layer. as well as The indium-based thermally conductive interface material is attached to the nickel layer using the organic adhesive layer; The metallurgical bond between the indium-based thermal interface material and the integrated heat sink is formed during the reflow process subsequently performed by the end user.
12. The preparation method according to claim 11, characterized in that: The organic adhesive layer is applied by spraying, dipping, spin coating, printing or dotting.
13. The preparation method according to claim 11, characterized in that: The organic adhesive layer is dried after application at a temperature of 20 to 100°C for 10 seconds to 10 minutes.